Relação entre a fadiga muscular e a mudança da técnica de nado durante um exercício exaustivo no nado crawl - Bassan, Natália de Menezes [UNESP] (2014)
Muscle strength is an important factor of the evaluation and training aiming a better sport performance. In swimming, the impairment of technique, body alignment and the increase of drag during races have been related to the development of fatigue, which corresponds to the reduced capacity to produce force. The objectives of this study were: 1) To analyze the reliability of the isometric peak torque (IPT), concentric peak torque at 60°.s-1 and 180°.s-1 (CPT60 and CPT180, respectively) and the rate of force development (RFD) of elbow flexors (EF) and elbow extensors (EE); 2) To analyze the effect of an exhaustive exercise on the strength and power variables, and swim technique (stroke frequency - SF and stroke length - SL, stroke phases - A, B, C and D and the coordination index - IdC), and; 3) To analyze the relationship between the responses of neuromuscular parameters, technical indexes and stroke phases, in an exhaustive exercise performed in front crawl. Fifteen trained swimmers participated of this study, and were submitted to the following protocols: 1) Initially, the anthropometric measurements were obtained and afterward the familiarization to the dynamometer was performed and maximal 400-m trial, in a 25-m swimming pool to determine the aerobic performance (V400); 2) Strength tests in an isokinetic dynamometer, to determine the IPT, CPT60, CPT180 and RFD, performed immediately before and after a constant-speed test to exhaustion at 100%V400 (T1); 3) The same tests at the same sequence of the second day (T2). The mean speed (1.34 ± 0.09 m.s-1 and 1.35 ± 0.15 m.s-1, respectively) at T1 and T2 conditions was similar (p > 0.05). There was no significant difference on IPT, CPT60, CPT180 and RFD at T1 and T2 conditions for EF (p > 0.05). In the same way, there was no significant difference on IPT, CPT60, CPT180 and RFD at T1 and T2 conditions for EE (p > 0.05). There was significant correlation between T1 and T2 conditions for...